A novel high-Mn duplex twinning-induced plasticity lightweight steel with high yield strength and large ductility - Huihui Zhi; Jinshan Li; Lulu Li; Yihua Luo; Yanjing Su; Minjie Lai (Journal of Materials Research and Technology)
In this study, we report a novel high-Mn Fe–21Mn–6Al–4Si–1C (wt.%) duplex lightweight steel with concurrent chemical ordering and twinning-induced plasticity effects. This steel is capable of achieving an exceptional combination of strength and ductility following either cold-rolling and annealing at 1000 °C or subsequent short-term aging at 550 °C. In its as-annealed state, this steel primarily consists of γ-austenite and α-ferrite, with α-ferrite appearing as dispersed particles within fully recrystallized γ grains. Furthermore, L′12- and D03-type ordered nanodomains exist within these two phases, respectively. The aging treatment negligibly affects the size and volume fraction of both the γ-austenite and α-ferrite, yet it enhances the degree of ordering as well as the size and volume fraction of their ordered nanodomains, leading to a rise in yield strength from ∼800 to ∼1062 MPa and a decline in total elongation from ∼60.4% to ∼44.4%. The high yield strength of this steel originates from multiple strengthening mechanisms involving dislocation interactions with solute atoms, ordered nanodomains, γ grain boundaries and γ/α phase boundaries. This steel plastically deforms via planar slip during the initial stages. The rather small γ grain size, coupled with the presence of hard α-ferrite particles, fosters the dynamic slip band refinement (DSBR) effect, thereby enhancing the flow stress sufficiently to trigger deformation twinning in the steel during the later stages. The DSBR effect, combined with the progressive formation of deformation twins, stacking faults and Lomer-Cottrell locks, imparts pronounced strain hardenability to this steel, leading to its outstanding ductility.